CORRELATION BETWEEN STUDENTS'VOCABULARY MASTERY AND THEIR READINGCOMPREHENSION:a study in second grand of junior high school - Fajar Furqon, - (2012)
The study investigated the correlation between students' vocabulary master) and their reading comprehension. Data were collected from 34 second grade students. The test items of reading comprehension and vocabulary master) were given to the students to measure their level of reading comprehension and vocabulary master). The results were compared to find out the correlation between those variables. The findings showed that there was strong correlation between students* vocabulary mastery and their reading comprehension. The current studv concluded that students" experiences and reading strategies help the students to understand texts but vocabulary mastery was more contributive in helping the students to comprehend the texts.